Endoscopic ultrasound (EUS)-guided fine needle biopsy alone vs. EUS-guided fine needle aspiration with rapid onsite evaluation in pancreatic lesions: a multicenter randomized trial - Chen, Yen-I; Chatterjee, Avijit; Berger, Robert; Kanber, Yonca; Wyse, Jonathan; Lam, Eric; Gan, Ian; Auger, Manon; Kenshil, Sana; Telford, Jennifer; Donnellan, Fergal; Quinlan, James; Lutzak, Gregory; Alshamsi, Fatma; Parent, Josee; Waschke, Kevin; Alghamdi, Adel; Barkun, Jeffrey; Metrakos, Peter; Chaudhury, Prosanto; Martel, Myriam; Dorreen, Alastair; Candido, Kristen; Miller, Corey; Adam, Viviane; Barkun, Alan; Zogopoulos, George; Wong, Clarence (Endoscopy, 2021)
Background Endoscopic ultrasound-guided fine-needle aspiration (EUS-FNA) is the standard in the diagnosis of solid pancreatic lesions, in particular when combined with rapid onsite evaluation of cytopathology (ROSE). More recently, a fork-tip needle for core biopsy (FNB) has been shown to be associated with excellent diagnostic yield. EUS-FNB alone has however not been compared with EUS-FNA + ROSE in a large clinical trial. Our aim was to compare EUS-FNB alone to EUS-FNA + ROSE in solid pancreatic lesions. Methods A multicenter, non-inferiority, randomized controlled trial involving seven centers was performed. Solid pancreatic lesions referred for EUS were considered for inclusion. The primary end point was diagnostic accuracy. Secondary end points included sensitivity/specificity, mean number of needle passes, and cost.Results 235 patients were randomized: 115 EUS-FNB alone and 120 EUS-FNA + ROSE. Overall, 217 patients had malignant histology. The diagnostic accuracy for malignancy of EUS-FNB alone was non-inferior to EUS-FNA + ROSE at 92.2 % (95 %CI 86.6 %–96.9 %) and 93.3 % (95 %CI 88.8 %–97.9 %), respectively (P = 0.72). Diagnostic sensitivity for malignancy was 92.5 % (95 %CI 85.7 %–96.7 %) for EUS-FNB alone vs. 96.5 % (93.0 %–98.6 %) for EUS-FNA + ROSE (P = 0.46), while specificity was 100 % in both. Adequate histological yield was obtained in 87.5 % of the EUS-FNB samples. The mean (SD) number of needle passes and procedure time favored EUS-FNB alone (2.3 [0.6] passes vs. 3.0 [1.1] passes [P < 0.001]; and 19.3 [8.0] vs. 22.7 [10.8] minutes [P = 0.008]). EUS-FNB alone cost on average 45 US dollars more than EUS-FNA + ROSE.Conclusion EUS-FNB alone is non-inferior to EUS-FNA + ROSE and is associated with fewer needle passes, shorter procedure time, and excellent histological yield at comparable cost.